Metabolic and proliferation evaluation of human adipose-derived mesenchymal stromal cells (ASC) in different culture medium volumes: standardization of static culture - Simão, Vinícius Augusto; Evangelista-Ribeiro, Caetano Pedro [UNESP]; Brand, Heloisa [UNESP]; Lagass-Pereira, Lougan; Marques, Laís Fernanda; Benites-Aoki, Pedro Henrique [UNESP]; Nunes da Silveira-Antunes, Roseli; Tonso, Aldo; Ribeiro-Paes, João Tadeu [UNESP] (Elsevier, 2019)
Adipose-derived mesenchymal stromal/stem cells (ASC) have acquired a prominent role in tissue engineering and regenerative medicine. However, the standardization of basic culture procedures in this cellular type is still not well established according to the main qualitative cellular attributes. We evaluate the cell growth profile of human ASC in a different culture medium volumes and their nutritional composition utilizing static cultivation. Culture medium volumes (5, 10 and 15 mL/25 cm2) in T-flasks were evaluated by kinetic parameters and the metabolic composition was determined by biochemical analysis and Fourier transform infrared (FT-IR) absorption spectroscopy. 50% renewal of culture medium volume every 48 h was adopted. Immunophenotypic characterization and cell differentiation were performed. There was no difference (p > 0.05) in the kinetic parameters of cell proliferation between the culture medium volumes or in FT-IR composition. However, the concentrations of glucose, glutamine, lactate, and glutamate varied significantly during the cultivation process as a function of the medium volume. ASC presented specific antigens and differentiation potential of mesenchymal stromal/stem cells. It was concluded that the minimal culture medium volume (5 mL/25 cm2 in static culture) was sufficient to maintain the stability, potency, and growth of ASC, representing an economic and safe standardization for this cell culture process.
Keywords: Biochemical analysis; FT-IR; Kinetic evaluation; Medium composition; Standard cultivation; Stem cells